Climate Change and its Impacts on Social Structures in Marginalized Communities - Sabira Zitouni; Salima Abdeslam; Amar Boussakra (Ukrainian Policymaker)
This study addresses the topic of climate change and its effects on social structures in marginalized communities, highlighting the complex relationship between the environment and social development. The study suggests that climate change exacerbates poverty and social discrimination, which negatively impacts the capacity of marginalized communities to adapt to environmental changes. These communities are often more exposed to natural disasters, such as floods and droughts, resulting in the loss of essential resources such as water and food. Furthermore, the study discusses how basic services such as education and healthcare decline as a result of environmental crises. Additionally, the pressures on these communities intensify, leading to the breakdown of traditional social structures and an increase in conflicts over resources. The study emphasizes the importance of comprehensive actions to mitigate the effects of climate change by enhancing the adaptive capacity of marginalized communities, providing financial and technical support, and implementing policies that ensure social justice. In conclusion, the study stresses the need to integrate climate change issues into development plans to protect the rights of marginalized communities and achieve sustainable development.